ANALYSIS OF STUDENTS’ UNDERSTANDING OF ISLAMIC BANKING PRODUCTS AT STAI MAU’IZHAH TANJUNG JABUNG BARAT - Zuhratul Aulia (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
The sharia financial literacy index in Indonesia is still low, only at 8,11 percent and Islamic financial inclusion at 11,06 percent, including students in it. This article discusses the level of understanding of students, Department of Sharia Banking, STAI Mau’izhah Tanjung Jabung Barat. This research is a descriptive quantitative research, the data collection was carried out through observation, and questionnaires with a total of 64 respondents, then analyzed using descriptive quantitative analysis using SPSS statistical tools. The results showed that the level of student understanding of Islamic banking products, namely collection products, distribution products, and financial services products, generally students understand with a general level of understanding above 75 percent. However, students still need to increase their understanding of wadiah, musharaka, istisna, hawalah, and kafalah products. The steps that can be taken are through public lectures, seminars, workshops, and visits directly to Islamic banks